Prostate-specific antigen testing and opportunistic prostate cancer screening: a cohort study in England, 1998–2017 - Clift, AK; Coupland, CAC; Hippisley-Cox, J (Royal College of General Practitioners, 2021)
Background Prostate cancer is a leading cause of cancer- related death. Interpreting the results from trials of screening with prostate-specific antigen (PSA) is complex in terms of defining optimal prostate cancer screening policy. Aim To assess the rates of, and factors associated with, the uptake of PSA testing and opportunistic screening (that is, a PSA test in the absence of any symptoms) in England between 1998 and 2017, and to estimate the likely rates of pre-randomisation screening and contamination (that is, unscheduled screening in the ‘control’ arm) of the UK-based Cluster Randomised Trial of PSA Testing for Prostate Cancer (CAP). Design and setting Open cohort study of men in England aged 40–75 years at cohort entry (1998–2017), undertaken using the QResearch database. Method Eligible men were followed for up to 19 years. Rates of PSA testing and opportunistic PSA screening were calculated; Cox regression was used to estimate associations. Results The cohort comprised 2 808 477 men, of whom 631 426 had a total of 1 720 855 PSA tests. The authors identified that 410 724 men had opportunistic PSA screening. Cumulative proportions of uptake of opportunistic screening in the cohort were 9.96% at 5 years’, 22.71% at 10 years’, and 44.13% at 19 years’ follow-up. The potential rate of contamination in the CAP control arm was estimated at 24.50%. Conclusion A substantial number of men in England opt in to opportunistic prostate cancer screening, despite uncertainty regarding its efficacy and harms. The rate of opportunistic prostate cancer screening in the population is likely to have contaminated the CAP trial, making it difficult to interpret the results.